An evaluation of strategies for restoring a degraded New Zealand scallop fishery using stochastic dynamic simulation modelling. (1st December 2021) - Soliman, Tarek; Robertson, Thomas; McKenzie, Jeremy; Williams, James; Djanibekov, Utkur; Inglis, Graeme J.
Abstract: A decision-theoretical approach was used to evaluate strategies to rebuild a severely depleted scallop ( Pecten novaezelandiae ) populations in the Tasman Bay and Golden Bay of New Zealand. These strategies were: no intervention, cessation of seabed bottom contact fishing, and reduction of sediment and nutrient runoff from surrounding land through on-farm practices. Our approach combined outputs of estimated effects of on-farm practices on erosion and nutrient reduction with a stochastic dynamic model of the scallop populations. The most effective individual intervention is eliminating bottom contact fishing through dredging and trawling which increased scallop biomass on average by 73% compared to the no intervention scenario. Although on-farm practices have reduced sedimentation and nutrient runoff significantly (28–36% and 2%, respectively), they have no effect on scallop biomass if implemented individually and led to only marginal improvements in scallop biomass if implemented alongside cessation of bottom contact fishing (2–4%). Although our results showed, on average, substantial recovery in the scallop population when reducing seabed bottom contact and water pollution, the large uncertainty boundaries makes it unclear whether these improvements would be realized. The long-term success of such strategies will depend on the available habitat being able to sustain high densities of healthy scallop adults and recruits, a situation that has been posited in our analysis. Where scallop juvenile survival is compromised by sedimentation, nutrient pollution, or other exogenous influences, proposed interventions may be insufficient to aid recovery. Highlights: Strategies to rebuild a depleted scallop populations in New Zealand are evaluated. We use stochastic dynamic scallop population model with land-based interventions. Eliminating bottom contact fishing is the most effective intervention. Farming practices slightly improve scallop biomass.